Peran Forum Kerukunan Umat Beragama Dalam Membina Kerukunan Antar Umat Beragama(Studi Kasus Fkub Kota Surakarta) - Pramono, Agus; , Drs. M. DarojatAriyanto, M.Ag (2016)
Indonesia is a country that has a plurality, ranging from diversity in terms of ethnicity, race, culture, ethnicity, religion. Pluralism in religion happens because of the inclusion of the major religions in Indonesia. The development of these religions has made Indonesia as a religious nation, which is religious life can not be separated from society life and the nation of Indonesia. Even the State guarantees on freedom of religion, while the government is obliged to protect the population in implementing the teachings of religion and worship, as long as thy do not contrary to the legislation, not abuse or tarnish religion, and do not disturb peace and public order. The government should provide guidance and services to every people in implementing their religion peacefully, smoothly and orderly, both internally and inter-religiously. As a step to build, guide and maintain of harmony, government through the Joint Regulation of the Minister of Religious Affairs and Minister of the Interior No. 9 and 8 in 2006, facilitated the establishment of the forum ofreligious national harmony (Forum Kerukunan Umat Beragama), in every province and district or city. The problems are FKUB's real role in fostering inter-religious harmony, and position of FKUB in the success of such government programs as well as inhibiting factors of FKUB in doing their duties. Based on the analysis, there are some conclusions have obtained, Surakarta FKUB's roles in shaping the religious harmony first, conducting a dialogue with religious leaders and community leaders; second, aspirations of religious organizations and communities; third, delivering aspirations of religious organizations and the public in the form of recommendations to Surakarta Mayor Policy; fourth, providing a written recommendation on the approval of the establishment of houses of worship; and fifth, conducting information about legislation and policies in the field of religion. FKUB has a very strategic position in fostering inter-religious harmony for several reasons. First FKUB stands under the statelaw. Second FKUB receives financial support aslong as this PBM is still valid. Third, FKUB gets facilities support with whole equipmentsin accordance with need. Fourth,the membership of FKUB is a representation of each religion. Meanwhile FKUB inhibiting factors in creating religious harmony there are several factors, First, internal factors (understanding people) are blind fanatics, subjective thought, misinterpretation violation of rules / norms, wrong suspicion. Second,are external factors (inter) in the form of the establishment of houses of worship that are not relevan with the rules, religious broadcasting, foreign aid, interfaith marriage, religious festivals, and blasphemy. Keywords: FKUB role, harmony, religious communities